Unraveling the Light-Activated Reaction Mechanism in a Catalytically Competent Key Intermediate of a Multifunctional Molecular Catalyst for Artificial Photosynthesis - Zedler, Linda; Mengele, Alexander Klaus; Ziems, Karl Michael; Zhang, Ying; Waechtler, Maria; Gräfe, Stefanie; Pascher, Torbjoern; Rau, Sven; Kupfer, Stephan; Dietzek, Benjamin (Angewandte Chemie International Edition, 2019)
Understanding photodriven multielectron reaction pathways requires the identification and spectroscopic characterization of intermediates and their excited-state dynamics, which is very challenging due to their short lifetimes. To the best of our knowledge, this manuscript reports for the first time on in situ spectroelectrochemistry as an alternative approach to study the excited-state properties of reactive intermediates of photocatalytic cycles. UV/Vis, resonance-Raman, and transient-absorption spectroscopy have been employed to characterize the catalytically competent intermediate [(tbbpy)2RuII(tpphz)RhICp*] of [(tbbpy)2Ru(tpphz)Rh(Cp*)Cl]Cl(PF6)2 (Ru(tpphz)RhCp*), a photocatalyst for the hydrogenation of nicotinamide (NAD-analogue) and proton reduction, generated by electrochemical and chemical reduction. Electronic transitions shifting electron density from the activated catalytic center to the bridging tpphz ligand significantly reduce the catalytic activity upon visible-light irradiation.
CRIS-Team Scopus Importer:2023-04-20
Keywords: enzyme catalysis; rhodium; ruthenium; spectro-electrochemistry; ultrafast spectroscopy